2015
DOI: 10.1073/pnas.1505068112
|View full text |Cite
|
Sign up to set email alerts
|

Extinction reverses olfactory fear-conditioned increases in neuron number and glomerular size

Abstract: Although much work has investigated the contribution of brain regions such as the amygdala, hippocampus, and prefrontal cortex to the processing of fear learning and memory, fewer studies have examined the role of sensory systems, in particular the olfactory system, in the detection and perception of cues involved in learning and memory. The primary sensory receptive field maps of the olfactory system are exquisitely organized and respond dynamically to cues in the environment, remaining plastic from developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 55 publications
4
46
0
Order By: Relevance
“…A number of the M-PTSD specific functional enrichments are also highly plausible; for example, enrichment H3K27 acetylation peaks from a gene-set derived from DLPFC neurons (Girdhar et al, 2018), known to have a role in stress models and neuropsychiatric disorders (McEwen et al, 2015), including PTSD (Maddox et al, 2018). Our results highlight a potential shared genetic basis between olfaction and M-PTSD, in line with previous findings of differential olfactory 5 identification in individuals with combat-related M-PTSD compared to healthy controls (Vasterling et al, 2000); olfactory triggers for PTSD intrusion symptoms (Daniels and Vermetten, 2016); olfactory-based treatments for PTSD (Aiken and Berry, 2015); and the key role of olfaction in fear conditioning in animal models (Morrison et al, 2015). Given the significant genetic overlap between olfaction and PTSD, our results support the hypothesis that 10 differential sensitivity to odors may predispose to development of PTSD.…”
Section: Discussionsupporting
confidence: 90%
“…A number of the M-PTSD specific functional enrichments are also highly plausible; for example, enrichment H3K27 acetylation peaks from a gene-set derived from DLPFC neurons (Girdhar et al, 2018), known to have a role in stress models and neuropsychiatric disorders (McEwen et al, 2015), including PTSD (Maddox et al, 2018). Our results highlight a potential shared genetic basis between olfaction and M-PTSD, in line with previous findings of differential olfactory 5 identification in individuals with combat-related M-PTSD compared to healthy controls (Vasterling et al, 2000); olfactory triggers for PTSD intrusion symptoms (Daniels and Vermetten, 2016); olfactory-based treatments for PTSD (Aiken and Berry, 2015); and the key role of olfaction in fear conditioning in animal models (Morrison et al, 2015). Given the significant genetic overlap between olfaction and PTSD, our results support the hypothesis that 10 differential sensitivity to odors may predispose to development of PTSD.…”
Section: Discussionsupporting
confidence: 90%
“…The olfactory system is an ideal system to successfully address how experience with a salient environmental cue can exert influences across generations . Training mice to associate a specific odor (eg, Odor A) with a mild foot‐shock results in these mice developing fearful behavior toward Odor A and possessing increased neuroanatomical expression of odorant receptors that detect Odor A . From an intergenerational perspective, we have demonstrated that after mice have been exposed to Odor A + shock conditioning their naïve offspring possess a sensitivity to Odor A and increased neuroanatomical expression of odorant receptors that detect Odor A .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the form of plasticity we observe appears to employ a distinct mechanism from reports of fear conditioning influencing the proportional abundance of OSNs expressing ORs responsive to the fear-conditioned odor 2931 . In the case of fear conditioning to acetophenone, the number of OSNs expressing M71 appears to profoundly upregulate within just 3 weeks.…”
Section: Discussionmentioning
confidence: 64%